Taiwanese Political Parties can be Categorized by Face, by Those Who Reported Making Face-To-Trait Inferences - Hu, Shun-Fu; Chang, Chien-Kai; Chen, Yu-Chen; Chien, Sarina Hui-Lin (Frontiers in Psychology, 2016)
The present study aims to replicate and extend Rule & Ambady (2010)’s findings that Republicans and Democrats could be differentiated by face. In Experiment 1, undergraduates categorized 50 gray-scale full-face photos of candidates of the two major political parties in Taiwan, the Kuomingtang (KMT) and the Democratic Progressive Party (DPP). Using identical stimuli and procedure, Experiment 2 tested 25- to 57-year-olds. Experiment 3 tested undergraduates with cropped photos, Experiment 4, with photos devoid of the mouth and chin area. At the end of each Experiment, we interviewed the participants about the strategies used. Results showed that undergraduates could categorize KMT and DPP with accuracies significantly higher than chance in full-face photos (Exp.1), M = .524, p = .045, cropped photos (Exp.3), M = .534, p = .016, and photos devoid of the mouth-and-chin area (Exp.4), M = .530, p = .048. Adults aged between 25 and 57 could also categorize full-face photos (Exp.2), M = .557, p < .001. Analysis on strategy use revealed that the better-than-chance performance may be a unique contribution of those who reported making face-to-trait inferences. In sum, we replicated Rule and Ambady’s (2010) results in East Asian and found that face-to-trait inferences may be essential.